Interactive Multimedia Modules to Enhance Family Support in Hypertension Management: A Digital Health Approach - Sudarman, Sudarman; Dioso, Regidor III; Hassan, Hafizah Che; Asfar, Akbar; Matdoan, Riska Amelia (Universitas Pendidikan Indonesia, 2025)
Background: Hypertension remains a leading global risk factor for morbidity and mortality, with family support playing a critical role in adherence to lifestyle modifications and treatment. Digital health interventions offer scalable solutions to improve disease management, yet limited studies have explicitly integrated and evaluated family engagement as a core component.Objective: This study aimed to evaluate the effectiveness of interactive multimedia modules in enhancing family support, blood pressure control, and health-related quality of life among hypertensive adults compared with usual care.Methods: A quasi-experimental study with repeated measures was conducted among 200 adults with hypertension and their primary family caregivers recruited from outpatient clinics. Participants were assigned to either the intervention group (n = 100), which received interactive multimedia modules delivered via a mobile platform, or the control group (n = 100), which received standard clinic-based education. Outcomes included family support (Hypertension Self-Care Activity Level Effects–adapted questionnaire), blood pressure (validated digital sphygmomanometer), and quality of life (WHOQOL-BREF). Measurements were obtained at baseline, immediately post-intervention, and 12-week follow-up. Data were analyzed using two-way repeated measures ANOVA.Results: At baseline, no significant differences were observed between groups in sociodemographic or clinical characteristics (p .05). Over time, significant time × group interaction effects were observed for family support (F[2, 396] = 48.72, p .001, partial η² = 0.20), systolic blood pressure (F[2, 396] = 61.45, p .001, partial η² = 0.24), diastolic blood pressure (F[2, 396] = 52.13, p .001, partial η² = 0.21), and overall quality of life (F[2, 396] = 39.74, p .001, partial η² = 0.17). Participants in the intervention group demonstrated greater improvements in family support, clinically meaningful reductions in blood pressure, and significant increases in quality of life scores compared with the control group. Qualitative feedback confirmed high acceptability and usability of the modules.Conclusion: Interactive multimedia modules delivered via digital health platforms significantly improved family support, blood pressure control, and quality of life among hypertensive adults. Incorporating family caregivers into digital self-management interventions provides a scalable and sustainable strategy for enhancing hypertension outcomes. Further studies should evaluate long-term impacts, cost-effectiveness, and integration into primary care systems.